Pengaruh Bukti Fisik terhadap Kepuasan Customer Hotel Novotel Jakarta Cikini - Suwarta, Firdaus; Dito, Samuel Frans (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Physical evidence is one of the important things that can improve customer impressions in the use of services provided. Therefore, in running its business, the Novotel Jakarta Cikini hotel must pay attention to physical evidence so that it is always in good condition, starting from interior, furniture, and facilities available at the hotel. Therefore the impression or perception of guests staying at the hotel will increase and This will later create customer satisfaction from the guest. The purpose of this research is to find out how big the influence of physical evidence on customer satisfaction at Novotel hotels Jakarta Cikini and the method used is a quantitative method with data collection techniques using questionnaires, observation, and literature study. The number of samples in this study was as many as 100 people stayed at the Novotel Jakarta Cikni Hotel. From the results, the calculation of the coefficient of determination (R2) shows the influence of physical evidence on customer satisfaction by 35%. Meanwhile, the calculation results t test obtained a value of tCount>tTable, namely 7.270>1.660 with a sig value 0.000<0.05 means H1 is accepted and H0 is rejected. It can be concluded that the physical evidence variable has a significant effect on customer satisfaction at the Novotel Jakarta Cikini hotel.